Beauvericin (BEA) and enniatin B (ENNB)-induced impairment of mitochondria and lysosomes - Potential sources of intracellular reactive iron triggering ferroptosis in Atlantic salmon primary hepatocytes. (March 2022) - Søderstrøm, Sofie; Lie, Kai K; Lundebye, Anne-Katrine; Søfteland, Liv
Abstract: Beauvericin (BEA) and enniatin B (ENNB) are emerging mycotoxins frequently detected in plant-based fish feed. With ionophoric properties, they have shown cytotoxic potential in mammalian models. Sensitivity in fish is still largely unknown. Primary hepatocytes isolated from Atlantic salmon ( Salmo salar ) were used as a model and exposed to BEA and ENNB (0.05–10 μM) for 48 h. Microscopy, evaluation of cell viability, total ATP, total H2 O2, total iron content, total Gpx enzyme activity, and RNA sequencing were used to characterize the toxicodynamics of BEA and ENNB. Both mycotoxins became cytotoxic at ≥ 5 μM, causing condensation of the hepatocytes followed by formation of blister-like protrusions on the cell's membrane. RNA sequencing analysis at sub-cytotoxic levels indicated BEA and ENNB exposed hepatocytes to experience increased energy expenditure, elevated oxidative stress, and iron homeostasis disturbances sensitizing the hepatocytes to ferroptosis. The present study provides valuable knowledge disclosing the toxic action of these mycotoxins in Atlantic salmon primary hepatocytes. Highlights: BEA and ENNB-induced impairment of mitochondria, culminating in reduced ATP levels. BEA and ENNB-induced impairment of lysosomes. A dose-dependent increase in the GSH-dependent Gpx enzyme activity was observed following BEA and ENNB exposure. Cytotoxic levels of BEA significantly increased the intracellular iron content.